Creating a Health Data Marketplace for the Digital Health Era - Imtiaz Khan; Mohamed Maher; Anjum Khurshid (Blockchain in Healthcare Today)
The author posits that the establishment of a blockchain-based health data marketplace where EHR, IoMT, and wearable-derived data can be monetized by selling it to data consumers like medical professionals, researchers, regulators, third-party (e.g., AI service providers) and policymakers can solve this data centralization problem.